Development and validation of an analytical method for the determination of N-3-methoxybenzyllinoleamide in brain homogenate of Sprague Dawley rats by High Performance Liquid Chromatography - Rodrigo Moscoso Palacios (2020)
A rapid, sensitive, precise and accurate High Performance Liquid Chromatography method was developed and validated for the determination of N-3-methoxybenzyl-linoleamide levels in Sprague Dawley rat brain. During sample preparation, acetonitrile was used as extraction solvent and N-benzyl-palmitamide as internal standard. The analyte was separated on a Chromolith® Performance column with isocratic elution of acetonitrile-ultrapure water (80:20, v/v) at 1.0 mL/min and 40°C. Detection was performed using a diode array detector at a wavelength of 205 nm. The selectivity of the method was confirmed by the absence of interferences from endogenous compounds. The developed method was used to construct linear calibration curves over the concentration range of 250 and 10 000 ng/mL (R2 ≥ 0.9900). Using 500 μg of brain homogenate, the validated lower limit of quantification was 250.0 ng/mL. Intra- and inter-day accuracy and precision were within 15% of nominal concentrations. Likewise, the analyte and its internal standard proved to be stable during storage, sample preparation and chromatographic analysis.